Do public health services in Egypt help young married women exercise their reproductive rights?. (August 2015) - Abdel-Tawab, Nahla; Rabie, Tamer; Boehmova, Zuzana; Hawkins, Loraine; Saher, Sally; El Shitany, Atef
Abstract: Objective: To assess supply and demand of family planning services from a reproductive rights perspective among young married women (YMW) in Egypt. Methods: Data sources related to family planning included structured interviews with service providers (n = 216); an inventory of equipment and supplies (n = 40); exit interview s with YMW (n = 147); and focus group discussions (n = 12) with YMW, husbands, and mothers and/or mothers in law. YMW, husbands and mothers in law were not necessarily related. Results: Although family planning services were readily available and affordable, YMW had limited access to information and services. Shortfalls were noted regarding respect for privacy, choice of family planning method, access to fertility services, and premarital counseling. Few YMW had sufficient autonomy to make informed reproductive decisions. Effective accountability mechanisms and processes for redress were also lacking. Conclusion: Implementation of a rights-based approach and structural changes to family planning service delivery are recommended to empower YMW in Egypt to demand and exercise their reproductive rights.